EVALUATION ANALYSIS OF AIRLANGGA UNIVERSITY FACULTY OF VOCATIONAL EDUCATION’S BRAND EQUITY USING CUSTOMER BASED BRAND EQUITY CONCEPT - Ayu Febriyanti Puspitasari; Ida Setya Dwi Jayanti (TIJAB (The International Journal of Applied Business), 2017)
Indonesia is now facing a new order of global world in terms of economics, educations and other infrastructures. Therefore, Government focus on developing an education system which is not only based on academic and professional fields but also vocational fields during the last decade. Brand is the identity of a product that can be used as a measurement of its quality. The concept is customer based brand equity (CBBE) which will be adopted in this study.This study aims to determine the strength of Airlangga University Faculty of Vocational Education Education’s brand equity.This study is using descriptive quantitative research approach. It describes the consumer assessment. In this case is the brand equity stakeholder’s institution Airlangga University Faculty of Vocational Education.These results indicate that brand awareness of this institution’s stakeholder is good. Based on the data, more than 60 respondents from a total of 77 respondents has already knew the existence of Airlangga University Faculty of Vocational Education. In addition, Stakeholders Faculty of Vocational Education already have brand loyalty to their institution. Therefore, they are willing to promote and give more contributions to Airlangga University Faculty of Vocational Education in order to become a better faculty. Airlangga University Faculty of Vocational Education has a strong brand image in the perception of their stakeholders. Concerning that the Faculty of Vocational Education is an applied science faculty, this institution consists of the entire course both Diploma III and Diploma IV at Airlangga University. Last, Stakeholders have a good perception related with the quality of Airlangga University Faculty of Vocational Education in order to create graduates or alumnae which is ready to work.The conclusion of this study is the strength of Airlangga University Faculty of Vocational Education’s brand equity in the perception of their stakeholders are good in fact. Airlangga University Faculty of Vocational Education has a strong image as a faculty of applied science which consists of the entire course both Diploma III and Diploma IV at Airlangga University. Keywords: Brand Equity, Customer Based Brand Equity, Faculty of Vocational Education Education, Airlangga University